Quantifying physiological health efficiency and benefit threshold of greenspace exposure in typical urban landscapes - Jin, Yuenan; Yu, Zhaowu; Yang, Gaoyuan; Yao, Xihan; Hu, Mingming; Remme, R.P.; van Bodegom, P.M.; Morpurgo, Joeri; Huang, Yunfeng; Wang, Jingyi; Cui, Shenghui (Environmental pollution (1987), 2024)
Although greenspace exposure has physiological health benefits, there is insufficient research on the threshold effect of health benefits in typical urban landscapes. Here we selected five typical urban landscapes (open greenspace, semi-closed greenspace, closed greenspace, bluespace, grey space) in 15 urban parks in Xiamen, China, and applied the physiological health threshold model to calculate the efficiency threshold and benefit threshold of greenspace exposure by continuously monitoring the changes of two physiological indicators-electroencephalography (EEG) and heart rate (HR). (1) The EEG threshold results show that compared with greenspace exposure, bluespace exposure can reach the physiological health efficiency threshold faster (4–5 min) but does not show an advantage in terms of benefit threshold. The more open the greenspace, the faster it can reach the efficiency threshold (5–6 min), but the higher the canopy density of the (closed) greenspace, the shorter the time to reach the efficiency threshold (8–9 min). (2) The HR threshold shows that bluespace and open greenspace are the fastest to reach the efficiency threshold (1 min), with the remaining greenspace reaching it after 6–7 min. The benefit threshold was reached faster in the bluespace (11 min) than in the greenspace (18–21 min), and the degree of openness of the greenspace has no significant effect on the speed of benefit thresholds. (3) Combining the results of EEG and HR thresholds, it can be seen that bluespace is better at reducing stress, while open greenspace can reach efficiency thresholds more quickly. This study confirms the physiological health threshold model, offering a reference for urban greenspace planning to enhance residents' stress management and health. [Display omitted] •The physiological health threshold of 5 typical urban landscapes was calculated.•The blue space reached the efficiency threshold within 5 min in stress recovery, better than green and grey spaces.•The more open the green space, the faster the efficiency threshold is reached.•The proposed framework based on “reality-virtual” and “subject-object” dimensions in Exposure ecology is enriched.